The Indian Pharmaceutical Sector : Issues and Options for Health Sector Reform - Govindaraj, Ramesh (Washington, DC: World Bank, 2013)
This report assesses the pharmaceutical sector in India, particularly focusing on four key issues related to the production, procurement, and distribution of drugs in India: a) availability, b) affordability; c) quality, and d) the rational use of drugs. The results of a survey of three states indicate considerable variation across states in the above four areas in both public and private sectors. The report concludes that problems with the availability, affordability, and rational use of good quality, cost-effective, essential drugs have persisted in most parts of India, and that these health-related issues need be addressed as a priority. An overarching recommendation is the need to focus on strengthening the implementation and regulation of the pharmaceutical sector at the state level, rather than on simply introducing new regulations. Adequate pharmaceutical quality assurance needs to be particularly emphasized as, in its absence, other reform measures could be rendered moot. Similarly, the rational use of drugs needs to be emphasized as it is likely to yield significant cost savings to the government and to consumers, in addition to its positive impact on health.